Evaluation of the acceptance and efficacy of a bespoke sun protection package for persons with oculocutaneous albinism living in Malawi - Gilaberte, Yolanda; Mzumara, Tenganawo E.; Manjolo, Sunganani P.; Kaseko, Ndamiwe; Bagazgoitia, Lorea; Fuller, L. Claire; Soto, Mafalda (International journal of dermatology, 2022)
Introduction Skin cancer is the main cause of death in persons with albinism (PWA) in Africa. Education would minimize sun damage. Objective To evaluate the efficacy and acceptance of a photoprotection educative and sunscreen (Umozi Max) package designed for PWA in reducing sunburns and skin cancer. Patients and Methods A multicenter, noncontrolled, before‐and‐after, interventional study was conducted in PWA > 12 years of age, from February to May, 2019, in Malawi. During the baseline and the follow‐up visits (at 8 and 15 weeks), subjects received an educational program designed to PWA and use of Umozi Max. At every visit, photoprotection behavior and knowledge were checked and cutaneous lesions were recorded. Univariate and bivariate analysis were performed. Results A total of 210 PWA were analyzed, 50% males, with a mean age of 24.5 (SD 11.29) years. The percentage of people using sun protective clothing increased from 80% to 100% and sunscreen from 81.9% to 99.5%. People avoiding the midday sun increased by 38.9% (P < 0.05). Participants that erroneously applied the sunscreen at night diminished from 40% to 4% (P < 0.001). Absent erythema on the face increased from 40% to 90% (P < 0.05). The percentage of patients with actinic keratoses (AK) on all locations significantly decreased during the study. All the participants preferred Umozi Max to previously used sunscreens. The satisfaction with the program was unanimous. Conclusion The educational program enhanced the use of all photoprotection measures, improved behaviors, and decreased the incidence of solar erythema and contributed to decreasing the incidence of new AKs.